Church, state, and citizen: Christian approaches to political engagement - Joireman, Sandra Fullerton (Oxford University Press, 2009)
Introduction / Sandra F. Joireman -- The Catholic tradition and the state : natural, necessary, and nettlesome / Robert B. Shelledy -- Lutheranism and politics : Martin Luther as a modernizer, but for the devil / Timothy J. Lomperis -- Reformed ... and always reforming? / James W. Skillen -- Anabaptists nd the state : an uneasy coexistence / Sandra F. Joireman -- The Anglican tradition : building the state, critiquing the state / Leah Seppanen Anderson -- For the sake of conscience : some evangelical views of the state / Timothy Samuel Shah -- Pentecostalism : Holy Spirit empowerment and politics / Stephen M. Swindle -- Concluding reflections / Mark R. Amstutz